EAVLD 2024 - 7th Congress of the European Association of Veterinary Laboratory Diagnosticians - the Editors (Italian Journal of Food Safety)
This abstract book contains the abstracts presented at the 7th Congress of the European Association of Veterinary Laboratory Diagnosticians.